Application of Finger Grasp Relaxation Therapy in Postoperative Hemorrhoidectomy Patients with Acute Pain in The Teratai Room of RSUD Prof. Dr. Margono Soekarjo Purwokerto - Shindy Ayuning Prahesti Shindy; Indri Heri Susanti (LPPM Universitas Harapan Bangsa, 2024)
Background: This study explores the use of finger grasp therapy to relieve pain in post-hemorrhoidectomy patients at RSUD Prof. dr. Margono Soekarjo Purwokerto. Objective: The purpose of this study was to determine the effect of finger grasping relaxation therapy on acute post-hemorrhoidectomy pain at Prof. Dr. Margono Soekarjo Purwokerto Hospital. Method: this research method uses a descriptive, paper-based approach, sampling using purposive sampling conducted on 1 patient. Data was collected through interviews, physical examination, and observation. Results: There is a decrease in pain from a scale of 6 (moderate) to 3 (mild) in the implementation for 3 days Conclusion: Finger grasping therapy as a non-pharmacological method in reducing post-hemorrhoidectomy pain